Don't blink [large type] : a novel - Patterson, James, 1947- (Little, Brown, 2010)
After he witnesses a hit on a mob lawyer that sparks an all-out mafia war, reporter Nick Daniels captures a key piece of evidence and launches a relentless investigation, during which he endures humiliation, threats, and violence.